1985
DOI: 10.1159/000212680
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on the Orcadian Rhythms of 23 Liver or Brain Enzymes from C57BL/6J Mice

Abstract: Mice were standardized to 12 h of light exposure alternating with 12 h of darkness and were fed ad libitum. The mice in the first group were 8 weeks old and in the other 104–116 weeks old. Subgroups of 7 animals from each age group were killed at 6 circadian stages. Enzyme activities of 23 enzymes from liver or brain were measured by an analysis of variance for each age group. All but 1 enzyme from young mice, and all but 9 from older mice showed significant changes over time (p < 0.01). The data from the 22 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Additionally, maintenance of enzyme activity and regulation of these rhythms often deteriorate with aging (24). We observed that while food consumption in AL (BN x F344)F 1 rats peaked during the dark span, considerable feeding also occurred during the light span.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, maintenance of enzyme activity and regulation of these rhythms often deteriorate with aging (24). We observed that while food consumption in AL (BN x F344)F 1 rats peaked during the dark span, considerable feeding also occurred during the light span.…”
Section: Discussionmentioning
confidence: 73%